A patient with medullar lesion and dissocial personality disorder - Neciosup-Tomé, Verónica D. (2019)
Medullar lesion is a major, severe, incapacitating and devastating condition that affects all personality structure. We present here the case of an admitted patient with a traumatic medullary lesion and dissocial personality disorder. The intellectual level and clinical patterns of personality were evaluated to contribute to a better understanding of the rehabilitation process.